Insect pests of groundnut (Arachis hypogaea L.): Current status and management approaches: INSECT PESTS OF GROUNDNUT : CURRENT STATUS AND MANAGEMENT APPROACHES - SNEHA SHARMA; CHETHANKUMAR M; VISHAW DEEP SHARMA; ARCHANA ANOKHE; P DURAIMURUGAN; MANOJ KUMAR YADAV (Journal of Oilseeds Research, 2025)
Groundnut (Arachis hypogaea L.) is a major oilseed, food, and fodder crop of tropical and subtropical regions, contributing substantially to nutritional security, farm income, and agro-industrial development. Its productivity is seriously constrained by a complex of insect pests that cause yield losses through direct feeding on foliage, flowers, pegs, and pods, transmission of viral diseases, and indirect damage predisposing pods to Aspergillus spp. infection and aflatoxin contamination. Important pests include defoliators such as tobacco caterpillar (Spodoptera litura F.) and red hairy caterpillar (Amsacta albistriga Walker), sucking pests like aphids (Aphis craccivora Koch), leafhoppers (Empoasca kerri Pruthi), thrips (Scirtothrips dorsalis Hood), and soil-dwelling pests such as white grubs (Holotrichia spp.) and termites. This review synthesizes information on the month-wise incidence, biology, and seasonal abundance of major groundnut insect pests in relation to crop phenology and agroclimatic conditions. The taxonomic status, key damage symptoms, and economic importance of each pest are summarized to aid accurate diagnosis and timely management. Emphasis is placed on evidence-based integrated pest management (IPM) approaches, including cultural and host plant resistance measures, conservation of natural enemies, pest monitoring using pheromone and light traps, and need-based insecticide application based on economic threshold levels. The review provides a practical framework for stage-specific pest surveillance and sustainable pest management in groundnut-based agro-ecosystems.